2017
DOI: 10.3389/fphar.2017.00309
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 in Paraventricular Nucleus Mediates Visceral Hypersensitivity Induced by Maternal Separation

Abstract: Neonatal maternal separation (MS) is a major early life stress that increases the risk of emotional disorders, visceral pain perception and other brain dysfunction. Elevation of toll-like receptor 4 (TLR4) signaling in the paraventricular nucleus (PVN) precipitates early life colorectal distension (CRD)-induced visceral hypersensitivity and pain in adulthood. The present study aimed to investigate the role of TLR4 signaling in the pathogenesis of postnatal MS-induced visceral hypersensitivity and pain during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…As per their findings, separation for 3 h daily can develop somatic and visceral hyperalgesia as well [ 49 52 ]. Nevertheless, we have recognized that exposure to MS 3 h daily could not develop visceral hypersensitivity in adulthood, whereas separation for 6 h daily could successfully induce visceral hypersensitivity, which was contrary to the abovementioned results [ 51 , 52 ] and consistent with our previous reports [ 53 ]. We attributed this discrepancy to the distinction in time course of separation and animal species.…”
Section: Discussionsupporting
confidence: 85%
“…As per their findings, separation for 3 h daily can develop somatic and visceral hyperalgesia as well [ 49 52 ]. Nevertheless, we have recognized that exposure to MS 3 h daily could not develop visceral hypersensitivity in adulthood, whereas separation for 6 h daily could successfully induce visceral hypersensitivity, which was contrary to the abovementioned results [ 51 , 52 ] and consistent with our previous reports [ 53 ]. We attributed this discrepancy to the distinction in time course of separation and animal species.…”
Section: Discussionsupporting
confidence: 85%
“…Most studies in which animals underwent a second stress have reported an increase in TNF-α in RMS animals, although generally in non-blood tissues rather than blood. Regarding just the brain, an increase in TNF-α expression in RMS animals was reported in the hippocampus (Amini-Khoei et al, 2017;Han et al, 2019;Pinheiro et al, 2015;Zhu et al, 2017), although in Han et al (2019), this difference was not tested statistically; the PFC (Ganguly et al, 2019;Pinheiro et al, 2015), although only in males but not females in Ganguly et al (2019); the PVN (Tang et al, 2017); the striatum (Dallé et al, 2017); and the nucleus accumbens in males but not females (Ganguly et al, 2019). Several studies, however, did not find any effect of RMS in the hippocampus (Viola et al, 2019;Wang et al, 2017) and PFC (Amini-Khoei et al, 2019;Viola et al, 2019).…”
Section: Long-term Effects Of Rms In the Presence Of Later-life Stressmentioning
confidence: 99%
“…Indeed, increased circulating levels of IL-1β (71) and IL-6 (179) have been reported in MS animals. In addition, MS offspring display neuroinflammatory marks such as increased Tnfa , Il-1b and Tlr4 expression or increased reactive oxygen species levels and decreased Il-10 expression in the hippocampus (71,75,87,114) , PFC (71) and PVN (180) . Recent studies have shown a decrease in the levels of the astrocytic marker GFAP (glial fibrillary acidic protein) in the PFC of MS animals (91) and the opposite effect in the locus coeruleus of MS females only (181).…”
Section: The Maternal Separation Modelmentioning
confidence: 99%